Distribution, abundance, and habitat requirements of endangered babblers in Mt. Kanlaon Natural Park, Negros Island, Philippines - Pios, Shaira Grace B.; Warguez, Dennis A.; Reintar, Andrew T.; Paguntalan, Lisa Marie J.; Jakosalem, Philip Godfrey C. (2016)
A study on the distribution, abundance, and habitat requirements of flamed-templed babbler (Dasycrotapha speciosa) and Negros-striped babbler (Stachyris nigrorum) in Mt. Kanlaon Natural Park was conducted from 18 May to 2 June 2015. A total of 44.5 km of transects were surveyed using a combination of line transect and point count methods while 567 circular plots measuring 30mx30m were established for habitat assessment. A total of 27 individuals of the flame-templed babbler were recorded in habitat types occuring from 604-1,078 masl while 14 individuals of the Negros striped-babbler was encountered in primary forest and secondary montane forest from 1,105-1,927 masl. D. speciosa was abundant in secondary lowland forest (n=16) while S. nigrorum was abundant in secondary montane forest (n=8). The presence of D. speciosa in plantation denotes that this forest serves as temporarily habitat for this babbler. Both logistic regression analysis and Poisson distributions showed that increased percentage of climbing bamboos and trees with 16-20 m height and decreased elevation implied increased likelihood of the occurence and abundance od D. speciosa.
Keywords: Bird conservation; Mt. Kanlaon Natural Park